Motivation of Students of The Faculty of Teacher Training and Education In Participating In Religious Learning and Worship Muamalah Model Baitul Arqam University of Muhammadiyah Surakarta - Saifudin; Ahmad Nurrohim; Muthoifin; Yeti Dahliana; Fuadi; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The objectives to be achieved in this study are to find out: Motivation of Students of the Faculty of Teacher Training and Education in participating in Islamic Studies Learning 1 and 2 Baitul Arqam Model of the University of Muhammadiyah Surakarta. The type of research that the author conducts is in the form of field research using a qualitative approach, namely research whose procedures produce descriptive data in the form of written or spoken words from people and actors observed. The methods used to collect data are: First, the guided interview method (Guide interview) is an interview conducted by the interviewer with a series of complete and detailed questions. Second, the questionnaire method is a data collection technique carried out by giving a set of questions or written statements to respondents to answer